2002
DOI: 10.1152/ajpheart.00598.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular glutathione peroxidase deficiency and endothelial dysfunction

Abstract: Cellular glutathione peroxidase (GPx-1) is the most abundant intracellular isoform of the GPx antioxidant enzyme family. In this study, we hypothesized that GPx-1 deficiency directly induces an increase in vascular oxidant stress, with resulting endothelial dysfunction. We studied vascular function in a murine model of homozygous deficiency of GPx-1 (GPx-1 Ϫ/Ϫ ). Mesenteric arterioles of GPx-1 Ϫ/Ϫ mice demonstrated paradoxical vasoconstriction to ␤-methacholine and bradykinin, whereas wildtype (WT) mice showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 40 publications
7
134
0
3
Order By: Relevance
“…GPx-1 may also provide protection from the toxic effects of peroxynitrite through its peroxynitrite reductase activity. 48 Our results confirm the findings of Forgione et al 26 that deficiency of GPx-1 leads to impairment of endotheliumdependent vasodilator function in mice with normal plasma levels of tHcy. Forgione et al observed endothelial dysfunction with paradoxical vasoconstriction to endotheliumdependent agonists in mesenteric arterioles of Gpx1 Ϫ/Ϫ mice fed standard chow.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GPx-1 may also provide protection from the toxic effects of peroxynitrite through its peroxynitrite reductase activity. 48 Our results confirm the findings of Forgione et al 26 that deficiency of GPx-1 leads to impairment of endotheliumdependent vasodilator function in mice with normal plasma levels of tHcy. Forgione et al observed endothelial dysfunction with paradoxical vasoconstriction to endotheliumdependent agonists in mesenteric arterioles of Gpx1 Ϫ/Ϫ mice fed standard chow.…”
Section: Discussionsupporting
confidence: 90%
“…To minimize the potential influence of differences in genetic background, GPx-1-deficient mice were crossbred to C57BL6 mice (The Jackson Laboratory, Bar Harbor, Me) for at least 7 generations and then interbred to generate littermates that were wild type (Gpx1 ϩ/ϩ ), heterozygous (Gpx1 ϩ/Ϫ ), or homozygous (Gpx1 Ϫ/Ϫ ) for the mutated Gpx1 allele. Genotyping for the wild-type and mutated Gpx1 alleles was performed by polymerase chain reaction as described by Forgione et al 26 At the time of weaning, mice were placed on either a control diet (LM-485 chow, Harlan Teklad) or a high methionine diet (LM-485 chow and drinking water supplemented with 0.5% L-methionine). After 17 weeks of the experimental diet, mice were euthanized with sodium pentobarbital (75 mg IP).…”
Section: Micementioning
confidence: 99%
“…Thus a deficiency of GPx-1 may lead to a decrease in bioavailable nitric oxide via at least two mechanisms, an increase in reactive oxygen species and an increase in lipid hydroperoxides. In support of this hypothesis we have shown previously that mice deficient in GPx-1 have endothelial dysfunction owing to decreased bioavailable endothelium-derived nitric oxide; increased oxidative stress and increased lipid hydroperoxide generation as measured by increased tissue isoprostane F 2α -III and hepatic phospholipid hydroperoxide levels; and increased nitrosative stress, as indicated by increased immunostaining for 3-nitrotyrosine in aortic tissue of GPx-1 knockout mice compared to wild-type mice (36).…”
Section: Inhibition Of Cellular Antioxidant Enzymes By Homocysteinesupporting
confidence: 53%
“…41 In animals with targeted gene disruption of the GPX-1 gene, endothelial function was impaired. 42 Therefore, it is conceivable that subjects with a reduction in the plasma concentrations of circulating GPX-3 undergoing HSCT may be at increased risk of organ damage beyond day 100 following transplant. In the small cohort of subjects in this study we were unable to demonstrate an increased incidence of organ damage in those with concentrations of GPX-3 below 100 mg/ml (data not shown).…”
Section: Discussionmentioning
confidence: 99%